Microfluidic engineering of exosomes: editing cellular messages for precision therapeutics. Issue 12 (21st May 2018) - Zhu, Qingfu; Heon, Mikala; Zhao, Zheng; He, Mei
Abstract : This review examines scientific advancements of microfluidic technology for engineering exosomes and assesses future applications and perspectives in developing precision therapeutics, which can serve the community by identifying potential new research areas or technologies that are urgently needed in precision therapeutics. Abstract : Study of extracellular vesicles (EVs), particularly exosomes, holds significant promise; however, it is technically challenging to define these small and molecularly diverse nanovesicles. With intrinsic molecular payload and biodegradability, molecular engineering of exosomes opens new avenues for mediating cellular responses and developing novel nano-delivery systems in precision therapeutics. Microfluidic lab-on-chip technology is playing pivotal roles in this emerging field. In this review, we have examined scientific advancements of microfluidic technology for engineering exosomes and assessed future applications and perspectives in developing precision therapeutics; this can serve the community via identification of potential new research areas or technologies that are urgently needed in precision therapeutics.